The Effects of Abutment Taper, Length and Cement Type on Resistance to Dislodgement of Cement-Retained, Implant-Supported Restorations - Cynthia S. Petrie, DDS, MS,1 Gerald D. Woolsey, BS, DDS, MS,2 (Journal of Prosthodontics, 2003)
The purpose of this study was to compare recordings of mandibular movements obtained with a Denar mechanical pantograph to those obtained with a Denar computerized axiograph (Cadiax compact).